Urban Growth, Liveability and Quality Urban Design: Questions about the Efficacy of Urban Planning Systems in Auckland, New Zealand - Beattie, Lee; Haarhoff, Errol (Anglo-American Publications LLC, 2018)
Preventing sprawl and concentrating future urban growth at transit centres, typifies many urban planning strategies in a number of Australian, New Zealand and North America cities.  Newer iterations of these strategies also argue that compact development delivers public benefits by enhancing urban liveability through good urban design outcomes.  Where neoliberal economic conditions prevail, achieving these aims is largely dependent on market-driven development actions requiring the appropriate urban planning responses to ensure these outcomes.  However, there are growing concerns that urban planning approaches currently used are not effectively delivering the quality urban design outcomes expected and enhancing residents liveability.  This paper reports on an evaluation of three medium density housing developments located in areas designated for intensification in Auckland, New Zealand.  Examined is the extent to which the development outcomes are aligned with the statutory urban planning requirements for quality urban design. The results indicated contradictions and points to limitations of the statutory planning system to positively influence quality outcomes, leading to enhanced residents experiences.    References Adams, D. and Tiesdell, S. (2013) Shaping Places: Urban Planning, Design and Development. London: Routledge. Auckland City Council (1999) Auckland City Council District Plan: Isthmus Plan section. Auckland: Auckland City Council. Auckland Regional Council (1999), Auckland Regional Growth Forum: a vision for managing growth in the Auckland Region. Auckland: Auckland Regional Council. Auckland Regional Council. (2008) Proposed Plan Change 6 to the Auckland Regional Policy Statement. Auckland: Auckland Regional Council. Arenibafo, F. (2016). The Transformation of Aesthetics in Architecture from Traditional to Modern Architecture: A case study of the Yoruba (southwestern) region of Nigeria. Contemporary Urban Affairs (JCUA), 1(1), 35-44. Doi: 10.25034/1761.1(1)35-44 Barnett, J. (2003) Redesigning cities: principles, practices and implementation. Chicago: Planners Press. Beattie, L. and Haarhoff, E. Delivering quality urban consolidation on the urban fringe: A case study of University Hill, Melbourne, Australia. Journal of Urban Regeneration and Renewal 7(4): 329-342. Beattie, L. (2013) Evaluating District Plan in Auckland, New Zealand: Do they deliver their intended outcomes. PhD thesis, University of Auckland, Auckland, New Zealand. Beattie, L. (2011) The Auckland Spatial Plan: the challenge of implementation. Paper presented at the 4th World Planning School Congress; Perth, Australia. Beattie, L. and Haarhoff, E. (2011) Governance: how to achieve urban growth management in practice: a practitioner perspective. Paper presented at the International New Urbanism and Smart Growth Conference; Perth, Australia. Bunker, R., Gleeson, B., Holloway, D. and Randolph, B. (2002) The local Impacts of Urban Consolidation in Sydney. Urban Policy and Research, 20(2): 143-167. Buxton, M. and Tieman, G. (2005) Patterns of Urban Consolidation in Melbourne: Planning Policy and the Growth of Medium Density Housing. Urban Policy and Research, 23:2: 137-157. CABE (2008), Creating successful masterplans, London: Commission for Architecture and the Built Environment. Campoli, J. Made for Walking: Density and Neighborhood Form. Cambridge, MA: Lincoln Institute of Land Policy. CHRANZ (2011) Improving the Design, Quality and Affordability of Residential Intensification in New Zealand. Auckland: Centre for Housing Research Aotearoa New Zealand. Dixon, J. and Dupuis, A. (2003) Urban Intensification in Auckland, New Zealand: a challenge for new urbanism. Housing Studies 18(3): 353-369. Ericksen, N., Berke, P., Crawford, J. and Dixon, J. (2003) Planning for Sustainability: New Zealand under the RMA. Waikato: International Global Change Institute. Haarhoff, E., Beattie, L., Dixon, J., Dupuis, A., Lysnar, P. and Murphy, L. (2012) Future Intensive: Insights for Aucklandâs Housing.  Auckland: The University of Auckland/Transforming Cities. Haarhoff, E., Beattie, L., & Dupuis, A. (2016). âDoes higher density housing enhance liveability? Case studies of housing intensification in Aucklandâ. Cogent Social Sciences, 2(1). https://doi.org/10.1080/23311886.2016.1243289 Haarhoff, E. and Beattie, L. (2011) Questions about smart growth: a critical appraisal of urban growth strategies in three North American cities. Paper presented at the International New Urbanism and Smart Growth Conference; Perth, Australia. Ingram, G., Carbonnell, A., Hong, Y-H and Flint, A. (2009) Smart Growth Policies: an Evlauation of Programs and Outcomes. Cambridge, MA: Lincoln Institute of Land Policy. Jain, A. and Courvisanon, J. (2008) Urban Growth on the periphery: ad hoc policy visions and research neglect. Paper presented at the 32nd ANZRSAI Conference; Adelaide, Australia. Laurian, L., Crawford, J., Mason, G., Erickson, N., Kouwenhoven, P., Day, M. and Beattie, L, (2010) Evaluating the Outcomes of Plans. Environment and Planning B 37(4): 740-757. Laurian, L., Day, M., Backhurst, M., Berke, P., Ericksen, N., Crawford, J., Dixon, J. and Chapman, S. (2004) What Drives Plan Implementation? Plans, Planning Agencies and Developers. Journal of Environmental Planning and Management 47(4): 555-577. Lunt, N. and Davidson, C. (2003). Introduction: evaluate matters. In Lunt, N., Davidson, C. and Mc Kegg, K (eds) Evaluating Policy and Practice: A New Zealand Reader. Auckland: Pearson Education. McDougall, A. and Maharaj, V. (2012) Closing the Gaps on the urban fringe of Australia capital cities: an investment worth making. Australian Planner 48(3): 131-140. Ministry for the Environment. (2012) Medium density housing: case study assessment methodology. Wellington: New Zealand Government. Nikoofam, M., & Mobaraki, A. (2016). In Pursuit of Sustainable Strategic Long-term Planning Throughout Meta-postmodernism as New Perspective of Stylistic Design. Contemporary Urban Affairs (JCUA), 1(1), 45-55. Doi: 10.25034/1761.1(1)45-55 Newman, P. and Kenworthy, J, (1989) Cities and Automobile Dependence. Aldershot: Gower. Newman, P. and Kenworthy, J. (1999) Sustainability and Cities. Washington, DC: Island Press. New Zealand Government, (2010). Spatial Planning Options for the Auckland Council, Cabinet paper from the Minister for the Economic Development and Environment, Wellington, New Zealand. North Shore City Council (2003) North Shore City District Plan. Auckland: North Shore City Council. Phan, T., Peterson, J., and Chandra, S. (2009) Residential Intensification in a suburban fringe local government area, Casey, Melbourne Metropolitan area, Australia. Australasian Journal of Regional Studies 15(1): 81-100. Quastel, N., Moos, M. and Lynch, N. (2012) Sustainabilty-as-Density and the Return of the Social: The Case of Vancouver, British Columbia. Urban Geography 33(7): 1055-1084. Randolph, B. (2006) Delivering the compact city in Australia: current treads and future implications. Urban Policy and Research 24(4): 473-490. UK Government (2009) World Class Places: The Governmentâs Strategy for Improving Quality of Place, London: Department for Communities and Local Government. Waldner, L. (2008) Regional plans, local fates? How spatially restrictive regional policies influence county policy and regulations. Environment and Planning B: Planning and Design 35(4): 679 â 700.   Wiles, J.L, Rosenberg, M.W. and Kearns, R.A. (2005), Narrative analysis as a strategy for understanding interview talk in geograohic research, Area, 37 (1), 89-99. Woodcock, I., Dovey, K., Wollan, S., and Robertson, I. (2011) Speculation and Resistance: Constraints on Compact City Policy Implications in Melbourne. Urban Policy and Research 29(4): 343-362.